Magnetic Core-shell nanoparticles with molecularly imprinted polymers for selective adsorption and separation of adenine. (4th July 2019) - Yang, Rui-Xia; Peng, Qiao-Hong; Yang, Xin-Rui; Yu, Bing; Shen, You-Qing; Cong, Hai-Lin
Abstract: Magnetic Core-shell nanoparticles coated with an adenine-imprinted polymer layer were successfully synthesized. The morphology of the nanoparticles was characterized by transmission electron microscopy (TEM). The nanoparticles have a definite core-shell structure and an imprinted polymer layer. The adsorption, recognition and reusability of the molecularly imprinted nanoparticles were analyzed by static/dynamic adsorption, competitive adsorption and reproducibility experiment. The magnetic molecularly imprinted nanoparticles exhibit fast adsorption, high adsorption capacity, strong specificity and satisfactory recovery.